Cultivating Nationalism and Patriotism through History Education: A Case Study of K.H. Hasyim Asy'ari in Indonesian Islamic Senior High Schools - Miqdad Syukril Iman; Tsabit Azinar Ahmad (Indonesian Journal of History Education, 2026)
Abstract: This study critically examines the cultivation of nationalism and patriotism through history education in two Nahdlatul Ulama-affiliated Islamic senior high schools in Margasari, Indonesia, using K.H. Hasyim Asy'ari as the central figure for values transmission. Drawing on qualitative phenomenological research, the investigation explores how teachers plan and implement values education, how students perceive and internalise these values, and what obstacles constrain effective cultivation. The findings reveal that while schools demonstrate com-mitment to transmitting nationalist and patriotic values through diverse peda-gogical strategies and extracurricular activities, implementation remains con-strained by limited infrastructure, time constraints, student disengagement, and the absence of critical engagement with the historical complexity of K.H. Hasyim Asy'ari's political and religious positions. This study argues that meaningful val-ues cultivation in post-colonial Islamic education requires moving beyond transmission toward critical pedagogy that enables students to interrogate the relationship between religious identity, nationalism, and historical conscious-ness.   Abstrak: Studi ini mengkaji penanaman nasionalisme dan patriotisme melalui pendidikan sejarah di dua sekolah menengah Islam binaan Nahdlatul Ulama di Margasari, dengan menjadikan K.H. Hasyim Asy'ari sebagai tokoh sentral. Menggunakan pendekatan fenomenologis kualitatif, penelitian menelaah perencanaan dan pelaksanaan pendidikan nilai oleh guru, persepsi serta internalisasi siswa, dan kendala yang dihadapi. Temuan menunjukkan bahwa sekolah berkomitmen menanamkan nilai melalui strategi pedagogis dan kegiatan ekstrakurikuler, namun implementasi terkendala infrastruktur terbatas, alokasi waktu, rendahnya keterlibatan siswa, dan minimnya telaah kritis atas kompleksitas historis sikap politik-keagamaan K.H. Hasyim Asy'ari. Studi berargumen bahwa penanaman nilai bermakna dalam pendidikan Islam pascakolonial perlu melampaui transmisi menuju pedagogi kritis yang memungkinkan siswa mengkaji relasi identitas keagamaan, nasionalisme, dan kesadaran historis.